2009
DOI: 10.1007/s00056-009-9909-y
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich skelettaler und konventioneller Ver ankerungsmethoden bei der präoperativen Dekompensation einer skelettalen Klasse III

Abstract: Skeletal molar anchorage proved to be more effective than the conventional anchorage. Hence, skeletal anchorage is preferable, especially when patients are in serious need of preoperative decompensation. The anterior palate has proven to be an advantageous region for insertion in conjunction with the correct mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 20 publications
0
33
0
3
Order By: Relevance
“…[21][22][23][24][25] It has been recently suggested that TPA can control anchorage, especially when it is combined with TADs. [24][25][26] In segmented arch mechanics, canine retraction T-loops have been used to control anchorage during space closure by modulating moments of the posterior teeth/part of the T-loop. 3,10,11 The aim of this study was to compare anchorage loss between two groups of patients who were treated either with continuous arch or segmented arch technique using T-loops to close extraction spaces while TPA was used to support the upper first molars.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] It has been recently suggested that TPA can control anchorage, especially when it is combined with TADs. [24][25][26] In segmented arch mechanics, canine retraction T-loops have been used to control anchorage during space closure by modulating moments of the posterior teeth/part of the T-loop. 3,10,11 The aim of this study was to compare anchorage loss between two groups of patients who were treated either with continuous arch or segmented arch technique using T-loops to close extraction spaces while TPA was used to support the upper first molars.…”
Section: Introductionmentioning
confidence: 99%
“…Six of the included studies 2,11,32,36,38,40 were nonRCTs. Study scores ranged from 13 to 20 points out of 24.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Study scores ranged from 13 to 20 points out of 24. Significant limitations were identified for most of the studies, such as the retrospective enrollment of the sample 2,11,32,40 with nonconsecutive inclusion of patients 2,32,36 or unclear reports about inclusion criteria.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 2 more Smart Citations